Chill without thrill: A crossover study on whole-body cryotherapy and postmatch recovery in high-level youth basketball players - Pernigoni, M.; Perazzetti, A.; Digno, M.; Tessitore, A.; Kamandulis, S.; Conte, D. (International Journal of Sports Physiology and Performance, 2024)
Purpose To assess the effect of whole-body cryotherapy (WBC) on postmatch recovery in basketball.